Overall care-seeking pattern and gender disparity at a specialized mental hospital in bangladesh - Nuri, Nazmun Nahar; Sarker, Malabika; Ahmed, Helal Uddin; Hossain, Mohammad Didar; Dureab, Fekri; Agbozo, Faith; Jahn, Albrecht (Materia socio medica, 2019)
Introduction: - The National Institute of Mental Health (NIMH) is the only national level mental health institution in Bangladesh, with both academic and clinical functions, thus playing a crucial role in delivering specialized mental health care for the entire population. - - Aim: - This study examined the overall pattern of mental health care seeking, age and sex distribution of patients and mental health problems diagnosed in the facility. - - Methods: - Using a facility-based cross-sectional study design, secondary data was collected from various hospital records and reports from April 2001 to June 2016, and quantitatively analyzed. - - Results: - There has been a steady increase in the number of patients at NIMH over the years. Typically, female patients were about half in number compared to male patients and fewer in each age group and all disease categories except inpatients with neurotic, stress-related and somatoform disorders. The highest number of inpatients and outpatients were 15-30 years old and those with schizophrenia, schizotypal and delusional disorders. - - Conclusion: - Minors and females seeking care at NIMH were underrepresented, thus highlighting the need for interventions to improve access for these patients.
Gesehen am 13.11.2020